Preparation method of core-shell structure inert lithium powder and battery
Patent Information
- Application Number
- CN202611334551.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的一个目的在于提供一种包括核壳结构惰性锂粉的电池的制备方法,解决现有技术中补锂用锂粉稳定性不足且在电池中难以构建稳定离子-电子混合导电网络,导致电池首次库伦效率低及循环性能差的技术问题
1.提升储锂性能与抑制枝晶:脱合金反应形成LixM提供额外可逆储锂容量,纳米金属M作为成核位点促进锂均匀沉积,抑制锂枝晶生长。
Smart Images

Figure CN123018157A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, specifically to a method for preparing a core-shell structured inert lithium powder and a battery. Background Technology
[0002] In electrodeless lithium-ion batteries or sodium-ion batteries, lithium or sodium ions deposit or detach on the surface of the negative electrode current collector during charging and discharging. The negative electrode current collector replaces traditional negative electrode active materials such as graphite and silicon-carbon, resulting in higher energy density and thus becoming one of the main research directions for high-energy batteries. However, during charging, a solid electrolyte interphase (SEI) easily forms on the negative electrode surface. Simultaneously, side reactions may occur in the electrolyte or electrolyte solution during charge-discharge cycles. These processes consume active lithium or active sodium from the positive electrode, leading to a decrease in coulombic efficiency, thereby reducing battery capacity, energy density, and cycle life. Irreversible lithium loss is most pronounced during the first charge-discharge cycle; currently, the initial coulombic efficiency of traditional electrodeless lithium-ion batteries typically does not exceed 90%.
[0003] To address the aforementioned issues, existing technologies have introduced "pre-lithiation" or "lithiation replenishment" techniques. These techniques involve introducing metallic lithium or lithium compounds into the electrode material to compensate for irreversible lithium loss, thereby improving the battery's energy density and cycle stability. Metallic lithium possesses an extremely high theoretical capacity (3860 mAh g⁻¹). -1 With its low standard electrode potential (-3.04V relative to the standard hydrogen electrode), lithium metal powder is an ideal negative electrode for lithium replenishment. However, its high reactivity and susceptibility to reactions with air, moisture, or other impurities pose serious challenges to its direct use in terms of storage, operation, and cycle stability.
[0004] Existing technology discloses a micron-sized inert lithium powder, which achieves reduced lithium powder activity and can be used for negative electrode lithium replenishment by passivation treatment through coating the lithium powder surface with an alloy layer and a hard layer. However, this method still has the following limitations: the particle size is relatively large, making it impossible to form a uniform and continuous in-situ conductive network; the shell structure is simple, and it cannot be converted into nano-metals to form a stable ion-electron mixed conductive network during the first discharge; the cycle performance is limited, and it is difficult to buffer the volume expansion during the alloying-dealloying process, resulting in performance degradation under high rate or long cycle conditions.
[0005] Therefore, a novel core-shell structure of nano-inert lithium powder is still needed. By controlling the core particle size and shell composition, the reversibility of the first discharge, air stability, and synergistic optimization of the ion-electron hybrid conductive network during cycling can be achieved, thereby solving the shortcomings of existing technologies in terms of first coulombic efficiency, reversibility of lithium replenishment, and cycle life. Summary of the Invention
[0006] One objective of this invention is to provide a method for preparing a battery comprising a core-shell structured inert lithium powder, thereby solving the technical problems in the prior art where the stability of lithium powder used for lithium replenishment is insufficient and it is difficult to construct a stable ion-electron mixed conductive network in the battery, resulting in low initial coulombic efficiency and poor cycle performance.
[0007] Another objective of this invention is to improve the reversible capacity, cycle stability, and high-rate performance of the battery.
[0008] According to the purpose of this invention, a method for preparing a battery comprising core-shell structured inert lithium powder is provided, comprising the following steps: A predetermined mass fraction of inert lithium powder is added to the negative electrode mixing slurry. After mixing, a negative electrode layer slurry is obtained. After coating, drying and rolling, a negative electrode sheet loaded with the inert lithium powder is obtained. The negative electrode, electrolyte layer and positive electrode are stacked and arranged, and assembled into a battery cell using a housing; Activate the battery cell to prepare the battery; The inert lithium powder has a core-shell structure comprising a core layer and a shell layer. The core layer is at least one of lithium metal, lithium-tin alloy, lithium-magnesium alloy, lithium-aluminum alloy, lithium-silver alloy, lithium-bismuth alloy, lithium-gallium, or lithium-zinc alloy, and the average particle size of the core layer is any value between 50 nm and 500 nm. The shell layer is a metal oxide layer (MO) with a thickness of any value between 2 nm and 10 nm. x M is at least one metallic element selected from Zn, Sn, Bi, Ga, and In, and the oxide metal layer is ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3, or a mixture thereof; Preferably, the metal oxide layer MO in the shell x During the first discharge, it reacts with Li + A transformation reaction occurs to generate nano-metal M and Li₂O, wherein the nano-metal M and the Li₂O are... + A reversible alloy-dealloy reaction occurs during charge-discharge cycles to form Li. x M, to form a stable ion-electron hybrid conductive network in the negative electrode.
[0009] Preferably, M is Ga, and MO is... x The substance is Ga2O3, which undergoes a conversion reaction during the first discharge to generate metallic gallium (Ga). 0 The metal gallium Ga 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Ga, where 0 < x ≤ 2.
[0010] Preferably, M is In, and MO is x The substance is In2O3, which undergoes a conversion reaction during the first discharge to produce metallic indium (In). 0 The metal indium In 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x In, where 0 < x ≤ 3.
[0011] Preferably, M is a combination of Zn and Sn, and MO x The MO is ZnO, SnO2, ZnSnO3 or Zn2SnO4. x A conversion reaction occurs during the initial discharge to produce metallic zinc (Zn). 0 At that time, the metallic zinc Zn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Zn, where 0 < x ≤ 1; The MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, the metallic tin Sn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4.
[0012] Preferably, M is a combination of Bi and Sn, and MO x The MO is BiO2, SnO2, Bi2SnO3 or Bi2Sn2O7. x A conversion reaction occurs during the initial discharge to produce metallic bismuth (Bi). 0 At that time, the metallic bismuth Bi 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Bi, where 0 < x ≤ 3; the MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, the metallic tin Sn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4.
[0013] Preferably, wherein the MO xThe Young's modulus of the shell is any value between 140 GPa and 150 GPa, and the hardness is any value between 9 GPa and 11 GPa.
[0014] Preferably, the electronic conductivity of the shell is greater than or equal to 10. -3 S·cm -1 .
[0015] Another aspect of the present invention provides a method for preparing inert lithium powder, for preparing the core-shell structured inert lithium powder described in any of the above technical solutions, comprising the following steps: Under an inert atmosphere with a preset dew point, using a metal-organic precursor containing metal element M as the source, atomic layer deposition or chemical vapor deposition is performed on lithium metal powder with an average particle size of 50nm-500nm to obtain a shell layer with a thickness of 2nm-10nm covering the periphery of the core layer under preset conditions.
[0016] Preferably, the preset dew point is less than or equal to -60°C.
[0017] Preferably, in the preset conditions for shell deposition, the deposition temperature is any value between 120℃ and 175℃, the film growth rate per cycle is 0.10nm to 0.15nm, the number of depositions is any value between 5 and 60, and the deposition pressure is any value between 0.5kPa and 5kPa.
[0018] This invention also provides a core-shell structured inert lithium powder, comprising a core layer and a shell layer surrounding the core layer; the core layer is at least one selected from lithium metal, lithium-tin alloy, lithium-magnesium alloy, lithium-aluminum alloy, lithium-silver alloy, lithium-bismuth alloy, lithium-gallium, or lithium-zinc alloy, and the average particle size of the core layer is 50 nm-500 nm; the shell layer is a metal oxide layer (MO). x The thickness is 2nm-10nm, and M is at least one metal element selected from Zn, Sn, Bi, Ga, and In. The oxide metal layer MO x The metal oxide layer is ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3, or a mixture thereof; x Able to react with Li during the first discharge of the battery + A transformation reaction occurs to generate nano-metal M and Li₂O, and the nano-metal M can react with Li₂O. + During charge-discharge cycles, a reversible alloy-dealloy reaction occurs to form Li. x M.
[0019] The present invention also provides a battery prepared by any one of the preparation methods described in the first aspect above.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Improve lithium storage performance and suppress dendrite formation: Dealloying reaction forms Li x M provides additional reversible lithium storage capacity, and the nano-metal M acts as a nucleation site to promote uniform lithium deposition and inhibit lithium dendrite growth.
[0021] 2. Constructing a fast conductive network and reducing polarization: Nanoscale lithium cores enable MO x It is rapidly converted into highly dispersed nano-metals M and Li2O, forming a uniform ion-electron hybrid conductive network, which improves reaction kinetics and reduces polarization resistance.
[0022] 3. Enhanced air stability: 2-10nm thick MO x The oxide layer forms a continuous and dense protective layer, effectively blocking oxygen and moisture, significantly improving the air stability of inert lithium powder, and ensuring rapid start-up of the lithium replenishment reaction.
[0023] 4. Buffering volume changes and extending cycle life: The nano-core-shell structure buffers volume changes through a multi-step alloying potential platform, releases stress at the nanoscale interface, reduces the risk of structural damage, and improves electrode structure stability and battery cycle life.
[0024] 5. Reduced environmental requirements: MO x The protective layer gives lithium powder excellent air stability, allowing it to be operated without a strictly anhydrous and oxygen-free environment, simplifying production, transportation, and battery assembly processes, and reducing manufacturing costs and environmental control thresholds.
[0025] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0026] The following sections will describe some specific embodiments of the invention in detail by way of example and not limitation, with reference to the accompanying drawings. The same reference numerals in the drawings denote the same or similar parts or portions. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings: Figure 1 This is a schematic flowchart illustrating a method for preparing a battery comprising a core-shell structured inert lithium powder according to an embodiment of the present invention. Detailed Implementation
[0027] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0028] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.
[0029] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but preferably also includes steps or units not listed, or preferably includes other steps or units inherent to such process, method, product, or apparatus.
[0030] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0031] Figure 1 This is a schematic flowchart illustrating a method for preparing a battery comprising a core-shell structured inert lithium powder according to an embodiment of the present invention.
[0032] like Figure 1 As shown, the present invention provides a method for preparing a battery comprising core-shell structured inert lithium powder, comprising the following steps: Step S100: Add a preset mass fraction of inert lithium powder to the negative electrode mixing slurry, mix to obtain a negative electrode layer slurry, and after coating, drying and rolling, obtain a negative electrode sheet loaded with inert lithium powder. Step S200: The negative electrode, electrolyte layer and positive electrode are stacked and arranged, and assembled into a battery cell using the casing; Step S300: Activate the battery cell to obtain a battery; wherein the inert lithium powder has a core-shell structure including a core layer and a shell layer, the core layer is at least one of lithium metal, lithium tin alloy, lithium magnesium alloy, lithium aluminum alloy, lithium silver alloy, lithium bismuth alloy, lithium gallium or lithium zinc alloy, and the average particle size of the core layer is any value between 50nm and 500nm, and the shell layer is a metal oxide layer MO with a thickness of any value between 2nm and 10nm. xM is at least one metallic element selected from Zn, Sn, Bi, Ga, and In, and the oxide metal layer is ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3, or a mixture thereof, such that the oxide metal layer MO in the shell is... x During the first discharge, it reacts with Li + A transformation reaction occurs to generate nano-metal M and Li₂O, and nano-metal M and Li + A reversible alloy-dealloy reaction occurs during charge-discharge cycles to form Li. x M is used to form a stable ion-electron hybrid conductive network in the negative electrode. Here, the average particle size of the core layer can be 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, or 500nm, or any other value between 50nm and 500nm. The thickness of the shell layer can be 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, or 10nm, or any other value between 2nm and 10nm.
[0033] This application also provides a core-shell structured inert lithium powder, comprising a core layer and a shell layer covering the periphery of the core layer; the core layer is at least one selected from lithium metal, lithium-tin alloy, lithium-magnesium alloy, lithium-aluminum alloy, lithium-silver alloy, lithium-bismuth alloy, lithium-gallium, or lithium-zinc alloy, and the average particle size of the core layer is 50nm-500nm; the shell layer is a metal oxide layer MO. x The thickness is 2nm-10nm, M is at least one metallic element selected from Zn, Sn, Bi, Ga, and In, and the metal oxide layer MO is... x ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3 or mixtures thereof; oxidized metal layer MO x Able to react with Li during the first discharge of the battery + A transformation reaction occurs to generate nano-metal M and Li₂O, and nano-metal M can react with Li₂O. + During charge-discharge cycles, a reversible alloy-dealloy reaction occurs to form Li. x M.
[0034] In this embodiment, MO with a thickness of 2nm-10nm is constructed on the surface of a nanoscale lithium core. x An oxide metal layer is applied to allow MO to dissolve during the first discharge of the battery. x A conversion reaction occurs to generate nano-metal M and Li₂O, and during subsequent charge and discharge processes, nano-metal M and Li₂O are generated. + A reversible alloy-dealloy reaction occurs to form Li. xM, thus forming a stable ion-electron hybrid conductive network in situ within the negative electrode. The core-shell structure enables MO x The oxide metal layer creates a synergistic effect between air stability, ion conduction, and lithium replenishment activity: MO x The metal oxide layer can stabilize and protect the lithium core during battery assembly and storage. During the first discharge stage of the battery, it can be transformed into Li2O with lithium conduction capability and a nano-metal network with high electronic conductivity. In subsequent cycles, it provides additional reversible lithium storage and deposition nucleation sites through alloy-dealloy reaction, thereby simultaneously improving air stability, reducing interfacial polarization and improving lithium replenishment efficiency.
[0035] In this embodiment, due to the formation of dense MO on the surface of the lithium core x The oxide metal layer possesses high chemical stability and a dense structure, effectively preventing oxygen and moisture in the air from directly contacting the lithium core. This significantly reduces the spontaneous oxidation or hydrolysis of metallic lithium in air, improving the stability and storage safety of inert lithium powder in an air environment. Compared to lithium powder that achieves stability solely through a physical passivation layer, the oxide metal layer MO in this embodiment... x While maintaining its protective function, it can also be transformed into an electrochemically active structure during the electrochemical reaction process, thus avoiding the problem that traditional passivation layers consume lithium and cannot participate in electrochemical reactions.
[0036] In this embodiment, during the first discharge of the battery, MO x The oxide metal layer undergoes a transformation reaction to generate nano-metal M and Li₂O. Li₂O acts as a lithium-ion conductor, providing a lithium-ion transport channel, while the nano-metal M exhibits high electronic conductivity. Together, they form a continuously distributed composite structure at the nanoscale, thereby constructing an in-situ ion-electron hybrid conductive network at the anode interface. This hybrid conductive network significantly reduces the lithium-ion transport impedance at the anode interface, improves interfacial reaction kinetics, and thus enhances the electrochemical performance of the battery under high-rate charge-discharge conditions.
[0037] Furthermore, during subsequent charge-discharge cycles, the nano-metal M generated by the conversion reaction can react with Li. + A reversible alloy-dealloy reaction occurs to form Li. x M provides additional reversible lithium storage capacity in the negative electrode and can serve as a nucleation site for lithium deposition, promoting uniform lithium deposition and inhibiting lithium dendrite growth. Simultaneously, different metals M undergo alloying reactions at different potential ranges, forming multi-step alloying potential plateaus. This buffers volume changes and reduces electrochemical polarization during charge and discharge, further improving the battery's cycle stability and energy density.
[0038] In this embodiment, the particle size of the lithium core is controlled within the range of 50nm-500nm, and a MO layer with a thickness of 2nm-10nm is formed on its surface. x An oxide metal layer is formed, thus constructing a nanoscale core-shell structure. Because the lithium core size is in the nanoscale range, its specific surface area is significantly increased, resulting in higher MO during the first discharge of the battery. x When the oxide metal layer undergoes a conversion reaction, highly dispersed nano-metallic M and Li2O structures can be rapidly generated on the lithium core surface, thereby forming a uniformly distributed ion-electron hybrid conductive network throughout the entire negative electrode interface region, improving interfacial reaction kinetics and reducing polarization resistance. Simultaneously, MO... x By controlling the thickness of the oxide metal layer within the range of 2nm-10nm, it can not only form a continuous and dense protective layer that effectively blocks oxygen and moisture in the air from contacting the lithium core, thereby improving the air stability of the inert lithium powder, but also, because the thickness of the oxide metal layer is in the nanoscale range, it can quickly complete the conversion reaction in the first electrochemical reaction, avoiding the lithium ion diffusion path being too long due to an excessively thick oxide metal layer, thus ensuring that the lithium replenishment reaction can start quickly.
[0039] Furthermore, the nanoscale core-shell structure can effectively buffer the volume changes caused by alloying-dealloying reactions during electrochemical cycling. Since the nano-metal M generated by the conversion reaction is highly dispersed in the shell region, the stress generated during subsequent alloying can be released through the nanoscale interface, thereby reducing the risk of material structure damage and improving electrode structure stability and battery cycle life. Therefore, by controlling the lithium core particle size and MO... x Nanoscale control of the thickness of the oxide metal layer enables synergistic optimization of air stability, ion-electron hybrid conductive network construction, and lithium replenishment reaction kinetics, thereby further improving the overall electrochemical performance of the battery.
[0040] In other embodiments, when MO x When the thickness of the oxide metal layer is less than 2 nm, it is difficult to form a continuous and dense protective layer, while when the MO layer thickness is less than 2 nm, it is difficult to form a continuous and dense protective layer. x When the thickness of the oxide metal layer is greater than 10 nm, the lithium-ion diffusion resistance increases significantly. Therefore, controlling the shell thickness within the range of 2 nm to 10 nm can achieve a balance between air stability and electrochemical reaction kinetics.
[0041] In a further embodiment, M is Ga, MO x The gas is Ga2O3, which undergoes a conversion reaction during the first discharge to form metallic gallium (Ga). 0 , metal gallium Ga 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. xGa, where 0 < x ≤ 2. In this embodiment, due to the high electronic conductivity and good lithium alloying reactivity of gallium, a stable electron conduction network can be formed in the interface region after the first conversion reaction, thereby effectively improving the electron transport capability of the negative electrode interface. Simultaneously, the Ga-Li alloying reaction has good reversibility, enabling the material to provide additional reversible capacity during cycling and helping to maintain the continuous activity of the interface reaction. Furthermore, the Li formed during the alloying process of gallium... x Ga structures possess a certain degree of plasticity and good stress buffering capacity, which can alleviate volume changes during cycling to some extent, thereby reducing the risk of interface structure damage and improving the cycle stability of the battery.
[0042] In this embodiment, based on the Li-Ga binary phase diagram and reported stable lithium-gallium alloy phases, Ga can form alloy phases such as LiGa and Li2Ga during electrochemical lithiation. Among them, Li2Ga is a stable phase that is close to fully lithiated, with a maximum lithiation ratio of approximately Li / Ga = 2. Therefore, during battery charging and discharging, the value of x can continuously vary within the range of 0 < x ≤ 2 to represent the gradual formation of alloy phases with different degrees of lithiation by Ga under different charging and discharging states. The value range of x covers both partial lithiation states and stable phases that are close to fully lithiated, which can reasonably characterize the actual process of the reversible alloying reaction between Ga and Li.
[0043] In a further embodiment, M is In, MO x The substance is In2O3, which undergoes a conversion reaction during the first discharge to produce metallic indium (In). 0 Indium 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. x In, where 0 < x ≤ 3. In this embodiment, due to the high theoretical alloy capacity and excellent electronic conductivity of indium, the nano-indium metal generated after the first conversion reaction can construct a stable electronic conduction path in the interface region, thereby improving the electron transport efficiency of the electrode material and promoting the reaction kinetics of lithium ions at the interface. Simultaneously, the In-Li alloy system has a high lithium storage capacity, enabling this structure to provide high reversible capacity compensation during lithium replenishment, which is beneficial for improving the energy density of the battery. Furthermore, the nanoscale dispersed indium particles can buffer volume changes through the interface stress release mechanism during the alloying-dealloying process, thereby improving the material's structural stability and cycle life.
[0044] In this embodiment, according to the Li-In binary phase diagram, In and Li can form various stable lithium-indium alloy phases, such as LiIn, Li2In, and Li3In. Among them, Li3In is a stable phase that is close to fully lithiated, with a maximum lithiation ratio of approximately Li / In = 3. Therefore, during the battery charging and discharging process, the value of x can continuously vary within the range of 0 < x ≤ 3 to characterize the gradual transition of In from the unlithiated state to alloy phases with different degrees of lithiation. The value range of x can cover the main stable lithiated phases in the Li-In system, thus truly reflecting its electrochemical alloying process.
[0045] In a further embodiment, M is a combination of Zn and Sn, MO x The alloy is ZnO, SnO2, ZnSnO3, or Zn2SnO4, such that MO x A conversion reaction occurs during the initial discharge to produce metallic zinc (Zn). 0 At that time, metallic zinc Zn 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. x Zn, where 0 < x ≤ 1, MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, metallic tin Sn 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4. In this embodiment, MO x These are Zn-Sn composite oxides such as ZnO, SnO2, ZnSnO3, or Zn2SnO4, which undergo a conversion reaction during the first discharge to generate metallic Zn. 0 and Sn 0 The generated metallic Zn 0 It can react with Li during charging and discharging. + A reversible alloying reaction occurs to form Li x Zn (0 < x ≤ 1), while the metal Sn 0 Then it can be with Li + Formation of Li xThe alloy structure of Sn (0 < x ≤ 4) exhibits high lithium storage capacity and provides high reversible lithium storage capability. Zn alloying results in relatively small volume changes, contributing to structural stability during cycling. Through the synergistic effect of Zn and Sn, a synergistic optimization is achieved between capacity and structural stability. Furthermore, the Zn-Sn composite oxide, after conversion, forms a composite structure of multi-metal nanoparticles and Li₂O. This structure constructs a more stable ion-electron hybrid conductive network and effectively mitigates volume expansion during alloying through a multi-interface structure, improving the material's cycling stability and rate performance.
[0046] In this embodiment, according to the Li-Zn binary phase diagram, Zn and Li mainly form a LiZn alloy phase, with a maximum lithiation ratio of approximately Li / Zn≈1. Therefore, during electrochemical cycling, the lithiation range of Zn can be represented by 0<x≤1. Meanwhile, according to the Li-Sn binary system, Sn can form a phase close to Li during deep lithiation. 4.4 The lithium-rich alloy phase of Sn, namely Li x For Sn (0 < x ≤ 4), x within the above range can cover the main lithium-tin alloy phase formed by Sn during charge and discharge, and approach the fully lithiated state. Therefore, in the Zn-Sn composite system, through the synergistic effect of Zn and Sn, Zn can provide structural stability, while Sn can provide high lithium storage capacity. The above range of x values can reasonably reflect the degree of alloying of the two metals in electrochemical cycling.
[0047] In a further embodiment, M is a combination of Bi and Sn, MO x The materials are BiO2, SnO2, Bi2SnO3, or Bi2Sn2O7, so that MO x A conversion reaction occurs during the initial discharge to produce metallic bismuth (Bi). 0 At that time, metallic bismuth Bi 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. x Bi, where, 0<x≤3, MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, metallic tin Sn 0 During charge-discharge cycles, it interacts with Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4. In this embodiment, MO x Bi-Sn composite oxides such as BiO2, SnO2, Bi2SnO3, or Bi2Sn2O7 undergo a conversion reaction during the first discharge to generate metallic Bi. 0 and Sn0 Among them, Bi 0 It can react with Li during the cycle. + Formation of Li x Bi (0 < x ≤ 3) alloy, while Sn 0 Li can be formed x The Bi-Sn bimetallic system exhibits a high lithium storage capacity (0 < x ≤ 4). Due to Bi's high electronic conductivity and low alloying potential, it can rapidly establish electron conduction pathways after the conversion reaction, thereby enhancing the electron transport capability at the electrode interface. Simultaneously, Sn possesses a high lithium storage capacity, enabling the material to provide a large reversible capacity during cycling. Furthermore, the Bi-Sn bimetallic system can form a multi-component alloy structure during alloying. The stress-regulating effect between the different metals effectively buffers the volume expansion generated during cycling and reduces the risk of particle pulverization and interface damage, thus improving the structural stability of the material and the cycle life of the battery.
[0048] In this embodiment, according to the Li-Bi binary phase diagram, Bi can form a stable alloy phase Li3Bi during lithiation, corresponding to a maximum lithiation ratio of approximately Li / Bi = 3. Therefore, its lithiation range can be represented by 0 < x ≤ 3 during electrochemical cycling. The lithiation mechanism of Sn is consistent with the above embodiment, and it can form a phase close to Li in the deep lithiation state. 4.4 Sn is a lithium-rich alloy phase, and its reasonable lithiation range is usually represented by 0 < x ≤ 4. Therefore, in the Bi-Sn composite system, Bi can provide higher electronic conductivity and improve structural stability, while Sn can provide higher reversible lithium storage capacity. The above-mentioned range of x values can reasonably characterize its electrochemical alloying process.
[0049] In a further embodiment, MO x The Young's modulus of the shell is any value between 140 GPa and 150 GPa, and the hardness is any value between 9 GPa and 11 GPa. MO x The Young's modulus and hardness of the shell are mainly related to factors such as the type of oxide material, film density, crystal structure, and shell thickness. By selecting oxide metal materials with high structural rigidity and combining atomic layer deposition or chemical vapor deposition processes to control film density and nanostructure, MO... x The Young's modulus of the shell is stable in the range of 140 GPa-150 GPa, and the hardness is stable in the range of 9 GPa-11 GPa, thus ensuring good structural stability while guaranteeing the mechanical strength of the shell.
[0050] Furthermore, the high Young's modulus enables the shell to effectively resist volume changes caused by lithium insertion / extraction and alloying reactions during battery charging and discharging, thereby maintaining the integrity of the shell structure and reducing the risk of shell cracking or breaking. Meanwhile, the moderate hardness enables the shell to provide mechanical support while avoiding excessive embrittlement, thus playing a stable role in restraining and protecting the internal lithium core and the generated nano-metal particles during cycling.
[0051] In a further embodiment, the electronic conductivity of the shell is greater than or equal to 10. -3 S·cm -1 It can form a highly efficient ion-electron hybrid conductive network inside the negative electrode, ensuring the conductivity of nano-metal M and Li. + Achieving full and uniform reversible alloying-dealloying reactions during charge-discharge cycles improves the battery's reversible capacity, cycle stability, and high-rate performance.
[0052] In a further embodiment, the inert lithium powder is prepared by the following method: Under an inert atmosphere with a preset dew point, using a metal-organic precursor containing metal element M as the source, atomic layer deposition or chemical vapor deposition is performed on a lithium metal powder core layer with an average particle size of 50 nm-500 nm. Under preset deposition conditions, a metal oxide layer MO with a thickness of 2 nm-10 nm is formed on the surface of the lithium metal powder core layer. x The shell layer is then used to obtain the core-shell structured inert lithium powder.
[0053] In this embodiment, the preparation method of inert lithium powder firstly involves atomic layer deposition or chemical vapor deposition using a metal-organic precursor under an inert atmosphere, which enables the formation of continuous and dense MO layers with a thickness of 2nm-10nm on the surface of the nano-lithium core. x The shell layer constructs a uniform core-shell structure. This core-shell structure not only effectively blocks moisture and oxygen in the air, improving the air stability of inert lithium powder, but also rapidly generates a nano-metallic M and Li2O composite conductive network during the first discharge, providing an efficient ion-electron channel for the subsequent reversible alloying-dealloying reaction. At the same time, it buffers volume changes during cycling, improving the battery's lithium replenishment efficiency, kinetic performance, and cycle life.
[0054] In a further embodiment, the preset dew point is less than or equal to -60°C. By controlling the preset dew point of the inert atmosphere to less than or equal to -60°C, the risk of the core layer coming into contact with ambient moisture or oxygen can be significantly reduced, thereby ensuring the activity of the lithium core and the uniformity of the shell deposition, avoiding the generation of defects or by-products during the first discharge, and improving the air stability, conversion reaction efficiency and subsequent cycle performance of the inert lithium powder.
[0055] In a further embodiment, the preset conditions for shell deposition include a deposition temperature of any value between 120℃ and 175℃, a single-cycle film growth rate of 0.10nm to 0.15nm, a deposition count of any value between 5 and 60, and a deposition pressure of any value between 0.5kPa and 5kPa. That is, the shell deposition temperature can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, or 175℃, or any other value between 120℃ and 175℃, and the single-cycle film growth rate can be 0.10nm, 0.11nm, 0.12nm, 0.13nm, 0.14nm, or 0.1... The deposition depth can be 5nm, or 0.10nm-0.15nm. The deposition number can be 5, 10, 20, 30 or 60, or any other value between 5 and 60. The deposition pressure can be 0.5kPa, 1.0kPa, 1.5kPa, 2.0kPa, 2.5kPa or 3.0kPa, or any other value between 0.5kPa and 3.0kPa. This allows for the full reaction and uniform deposition of the shell material while ensuring the stability of the lithium core, thereby obtaining a controllable thickness, continuous and dense coating shell. This improves the protective effect of the shell on the lithium core and the structural stability, and is beneficial to the stable progress of subsequent electrochemical reactions.
[0056] The present invention also provides a battery prepared by the above-described battery preparation method.
[0057] The technical solution of this application will be further described below with reference to specific embodiments.
[0058] Example 1
[0059] This embodiment provides a method for preparing a battery based on core-shell structured inert lithium powder, specifically including the following steps: S1: Preparation of inert lithium powder: Under a dry Ar atmosphere with a dew point ≤ -60℃, atomic layer deposition (ALD) was performed on metallic lithium powder with an average particle size D50 = 100 nm, using trimethylgallium (Ga(CH3)3) as the metal-organic precursor and H2O as the oxygen source. The deposition conditions were: deposition temperature 150℃, deposition pressure 2.0 kPa, pulse time 0.5 s, purge time 5 s, 30 deposition cycles, and a single-cycle growth rate of 0.12 nm, ultimately obtaining a core-shell structured inert lithium powder with a shell thickness of 7 nm. The core layer of the inert lithium powder is metallic lithium, the shell layer is Ga2O3, the Young's modulus of the shell layer is 145 GPa, the hardness is 10 GPa, and the electronic conductivity is 1.2 × 10⁻⁶. -3 S·cm -1 .
[0060] S2: Preparation of negative electrode sheet: Add 3% by mass of the above-mentioned inert lithium powder to the negative electrode mixed slurry (by mass ratio, carbon fiber: binder: dispersant: solid electrolyte = 40:40:5:15), and mix evenly by high speed to obtain a negative electrode layer slurry; coat the negative electrode layer slurry onto the copper foil current collector, and dry at 80°C for 12 hours to obtain a coating thickness of 40 μm for the negative electrode sheet.
[0061] S3: Cell assembly: The above-mentioned negative electrode, separator and NCM811 positive electrode are stacked in sequence, electrolyte is injected, and after encapsulation, a soft-pack cell is obtained.
[0062] S4: Cell activation: The unactivated cell is charged to 4.2V with a constant current of 0.05C, and then discharged to 2.8V with a constant current of 0.05C to complete the activation and obtain the target battery.
[0063] Example 2
[0064] The only difference between Example 2 and Example 1 is that the coating thickness of the negative electrode is 60 μm.
[0065] Example 3
[0066] The only difference between Example 3 and Example 1 is that the coating thickness of the negative electrode is 20 μm.
[0067] Example 4
[0068] The only difference between Example 4 and Example 1 is that the shell thickness of the inert lithium powder is 10 nm, the deposition number is 50 times, and the single-cycle growth rate is 0.12 nm; the Young's modulus of the shell is 150 GPa, the hardness is 11 GPa, and the electronic conductivity is 1.0 × 10⁻⁶. -3 S·cm -1 The coating thickness of the negative electrode sheet is 100 μm; the remaining preparation steps, process parameters and parameters of the inert lithium powder core layer are completely consistent with those in Example 1.
[0069] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the inert lithium powder added to the negative electrode slurry was replaced with uncoated pure metallic lithium powder. The other preparation steps, process parameters and negative electrode coating thickness (40 μm) were the same as in Example 1.
[0070] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no lithium supplementer is added to the negative electrode slurry.
[0071] The electrical performance of the batteries in Examples 1-4 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1.
[0072] Table 1. Electrical performance test results of batteries in Examples 1-4 and Comparative Examples 1-2
[0073] According to the test results in Table 1, compared with Comparative Example 1 and Comparative Example 2, the first-cycle efficiency and 300-cycle capacity retention of each example using Ga2O3 as a lithium replenisher are significantly improved. In the range of Ga2O3 coating thickness of 20~100μm, the first-cycle efficiency of the battery shows a slight upward trend with the increase of coating thickness, but the excessive thickness (100μm) will cause a significant decrease in cycle stability. The coating thickness range of 20~60μm can balance excellent first charge and discharge efficiency and long cycle capacity retention.
[0074] In summary, this invention effectively solves the technical problems of insufficient stability of lithium powder used for lithium replenishment and difficulty in constructing a stable ion-electron hybrid conductive network by designing and applying core-shell structured inert lithium powder. It significantly improves the first-cycle efficiency, cycle stability and reversible capacity of the battery, while also improving the high-rate performance of the battery, and has good practical application value.
[0075] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0076] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a battery comprising core-shell structured inert lithium powder, characterized in that, include: A predetermined mass fraction of inert lithium powder is added to the negative electrode mixing slurry. After mixing, a negative electrode layer slurry is obtained. After coating, drying and rolling, a negative electrode sheet loaded with the inert lithium powder is obtained. The negative electrode, electrolyte layer and positive electrode are stacked and arranged, and assembled into a battery cell using a housing; Activate the battery cell to prepare the battery; The inert lithium powder has a core-shell structure comprising a core layer and a shell layer. The core layer is at least one of lithium metal, lithium-tin alloy, lithium-magnesium alloy, lithium-aluminum alloy, lithium-silver alloy, lithium-bismuth alloy, lithium-gallium, or lithium-zinc alloy, and the average particle size of the core layer is any value between 50 nm and 500 nm. The shell layer is a metal oxide layer (MO) with a thickness of any value between 2 nm and 10 nm. x M is at least one metallic element selected from Zn, Sn, Bi, Ga, and In, and the oxide metal layer is ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3, or a mixture thereof, such that the oxide metal layer MO in the shell layer... x During the first discharge, it reacts with Li + A transformation reaction occurs to generate nano-metal M and Li₂O, wherein the nano-metal M and the Li₂O are... + A reversible alloy-dealloy reaction occurs during charge-discharge cycles to form Li. x M, to form a stable ion-electron hybrid conductive network in the negative electrode.
2. The method for preparing a battery according to claim 1, characterized in that, M is Ga, and MO is... x The substance is Ga2O3, which undergoes a conversion reaction during the first discharge to generate metallic gallium (Ga). 0 The metal gallium Ga 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Ga, where 0 < x ≤ 2.
3. The method for preparing a battery according to claim 1, characterized in that, M is In, MO x The substance is In2O3, which undergoes a conversion reaction during the first discharge to produce metallic indium (In). 0 The metal indium In 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x In, where 0 < x ≤ 3.
4. The method for preparing a battery according to claim 1, characterized in that, M is a combination of Zn and Sn, and MO x The MO is ZnO, SnO2, ZnSnO3 or Zn2SnO4. x A conversion reaction occurs during the initial discharge to produce metallic zinc (Zn). 0 At that time, the metallic zinc Zn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Zn, where 0 < x ≤ 1; The MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, the metallic tin Sn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4.
5. The method for preparing a battery according to claim 1, characterized in that, M is a combination of Bi and Sn, and MO x The MO is BiO2, SnO2, Bi2SnO3 or Bi2Sn2O7. x A conversion reaction occurs during the initial discharge to produce metallic bismuth (Bi). 0 At that time, the metallic bismuth Bi 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Bi, where 0 < x ≤ 3; The MO x During the initial discharge, a conversion reaction occurs to generate metallic tin (Sn). 0 At that time, the metallic tin Sn 0 During the charge-discharge cycle, with the Li + A reversible alloy-dealloy reaction occurs to form Li. x Sn, where 0 < x ≤ 4.
6. The method for preparing a battery according to claim 1, characterized in that, The inert lithium powder is prepared by the following method: Under an inert atmosphere with a preset dew point, using a metal-organic precursor containing metal element M as the source, atomic layer deposition or chemical vapor deposition is performed on a lithium metal powder core layer with an average particle size of 50 nm-500 nm. Under preset deposition conditions, a metal oxide layer MO with a thickness of 2 nm-10 nm is formed on the surface of the lithium metal powder core layer. x The shell layer is then used to obtain the core-shell structured inert lithium powder.
7. The method for preparing a battery according to claim 6, characterized in that, The preset dew point is less than or equal to -60℃.
8. The method for preparing a battery according to claim 6, characterized in that, The preset conditions for shell deposition include a deposition temperature of any value between 120℃ and 175℃, a single-cycle film growth rate of 0.10nm to 0.15nm, a deposition number of any value between 5 and 60, and a deposition pressure of any value between 0.5kPa and 5kPa.
9. A core-shell structured inert lithium powder, characterized in that, The inert lithium powder comprises a core layer and a shell layer surrounding the core layer; the core layer is at least one of lithium metal, lithium-tin alloy, lithium-magnesium alloy, lithium-aluminum alloy, lithium-silver alloy, lithium-bismuth alloy, lithium-gallium, or lithium-zinc alloy, and the average particle size of the core layer is 50 nm-500 nm; the shell layer is a metal oxide layer (MO). x The thickness is 2nm-10nm, and M is at least one metal element selected from Zn, Sn, Bi, Ga, and In. The oxide metal layer MO x The metal oxide layer is ZnO, SnO2, ZnSnO3, Zn2SnO4, Bi2O3, Bi2Sn2O7, Ga2O3, In2O3, or a mixture thereof; x Able to react with Li during the first discharge of the battery + A transformation reaction occurs to generate nano-metal M and Li₂O, and the nano-metal M can react with Li₂O. + During charge-discharge cycles, a reversible alloy-dealloy reaction occurs to form Li. x M.
